The University of Ottawa Healthcare Symposium (UOHS) 2026 Pitch-O-Rama: Undergraduate Elevator Pitch Research Competition - Maryam Al-Zadjali; Donya Sobati (Undergraduate Research in Natural and Clinical Science and Technology Journal, 2026)
The University of Ottawa Healthcare Symposium (UOHS) is an undergraduate conference that highlights the role of interdisciplinary collaboration in healthcare. Now in its sixteenth year, UOHS brings together students and researchers from fields such as biomedical sciences, engineering, health policy, and digital health to explore current challenges and advancements in healthcare. The conference provides a platform for discussions on emerging technologies, healthcare delivery, and the integration of research into clinical practice. As part of the symposium, Pitch-O-Rama challenges students to present their research in a concise and engaging way. Participants explain the significance of their work in a short elevator pitch, demonstrating how their research contributes to healthcare innovation. Judges evaluate presentations based on clarity, originality, interdisciplinary impact, scientific rigour, and the ability to address a meaningful knowledge gap. The competition allows students to practice effective science communication and consider how their work connects with broader healthcare challenges. This abstract book features the top submissions from the 2026 competition, highlighting research from undergraduate students across various disciplines. For more details about UOHS and Pitch-O-Rama, please visit https://www.uohs-csuo.com/.